The Benefits of Learning English Syntax in Improving Students' Writing Skills: A Documentary Study - Tanjung, Nadila; Utama, Loudya Putri; Dalimunthe, Herika; Widyana, Airen; Saharani, Dea; Nasution, Tuti Alawiyah Ramadani (CV. Rayyan Dwi Bharata, 2024)
This study aims to analyze the benefits of grammar learning in improving students' writing skills, especially in an English-speaking environment. In the era of globalization, the ability to write English has become an important skill that students must have. However, many students still experience difficulties due to a lack of understanding of the correct syntactic structure. Syntax, a branch of linguistics that studies sentence structure, is important in helping students construct clear and coherent sentences. Using qualitative methods and literature research, this study examines findings from various literature sources, showing that understanding syntax can improve text integration and coherence, enrich the variety of sentence structures, and improve students' critical thinking skills. Based on the analysis, understanding grammar has a positive impact on the quality of students' writing, both technically and content-wise, and makes it easier for them to express ideas effectively.